2018
DOI: 10.1155/2018/8394370
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Pulmonary Exacerbation after Initiation of Lumacaftor/Ivacaftor Therapy in a CF Female with Complicated Lung Disease

Abstract: Novel targeted treatments for Cystic Fibrosis give rise to new hope for an ever-growing number of CF patients with various mutations. However, very little evidence and guidelines exist to steer clinical decisions regarding patients whose illness takes an unexpected course. In such cases, the benefits and risks of discontinuing these treatments must be carefully and individually weighed, since their long-term effects remain mainly uncharted territory. In this report we document the case of a homozygous F508del … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Popowicz et al did note a transient yet significant decline in pulmonary function soon after initiation of full‐dose LUM/IVA that persisted for 24 hours; however, at 1 month, lung function returned to baseline for all pwCF 16 . Likewise, respiratory events and treatment discontinuations were reported by Hubert et al as well as Hatziagorou et al; however, improvement in lung function was observed with continued treatment 17,18 . Taylor‐Cousar et al also reported respiratory events (e.g., infective pulmonary exacerbations, dyspnea, cough) requiring CFTR modulator treatment modification and/or discontinuation 19 .…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Popowicz et al did note a transient yet significant decline in pulmonary function soon after initiation of full‐dose LUM/IVA that persisted for 24 hours; however, at 1 month, lung function returned to baseline for all pwCF 16 . Likewise, respiratory events and treatment discontinuations were reported by Hubert et al as well as Hatziagorou et al; however, improvement in lung function was observed with continued treatment 17,18 . Taylor‐Cousar et al also reported respiratory events (e.g., infective pulmonary exacerbations, dyspnea, cough) requiring CFTR modulator treatment modification and/or discontinuation 19 .…”
Section: Resultsmentioning
confidence: 93%
“…There were no major safety concerns for pwCF and severe lung disease reported with use of IVA, TEZ/IVA, or ELE/TEZ/IVA. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Popowicz et al did note a transient yet significant decline in pulmonary function soon after initiation of full-dose LUM/IVA that persisted for 24 hours; however, at 1 month, lung function returned to baseline for all pwCF. 16 Likewise, respiratory events and treatment discontinuations were reported by Hubert et al as well as Hatziagorou et al; however, improvement in lung function was observed with continued treatment.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations